Sem Observations On Wear Mechanism Of Tin-Coated Hss Twist Drills When Drilling Mild Steel - Talib, R. J.; Saad, S.; M. Toff, M. R.; Hashim, A. H. (Penerbit UTM Press, 2004)
In This Study, High Speed Steel (HSS) Twist Drills Were Investigated For Mechanical Wear By Performing Drilling Test On The Work Piece Of Mild Steel Plate. Tin Coatings Onto The HSS Twist Drills Were Achieved By Employing Reactive Radio Frequency (R.F) Magnetron Sputtering Technique, Which Was Developed In-House. The Drilling Performance Tests Were Set At A Rotation Speed Of 1,600 Rpm, Feed Rate Of 20 Mm/Min, And Depth Of Cut Of 25 Mm. The Morphological Changes Of The Wear Surface Were Observed Using Scanning Electron Microscopy (SEM). Results Of Morphological Examination Showed That The Failure Mechanisms In Operation During Drilling Were Found To Be Adhesive And Thermal Wear Mechanism. This Paper Will Also Discuss Explicitly The Processes Of Adhesive And Thermal Wear Mechanism Generated During Drilling Of Twist Drill On Mild Steel Plate. Results Of Drilling Performance Test Showed That The Tin Coating Deposited On The HSS Twist Drill Had Improved Drill Life By More Than 2 Times As Compared With Uncoated Drill.